Marius Barbeau and Musical Performers - Keillor, Elaine (MUSICultures, 2004)
One of Marius Barbeau’s important contributions to heightening awareness of folk music traditions in Canada was his organization and promotion of concerts. These concerts took different forms and involved a range of performers. Concert presentations of folk music, such as those that Barbeau initiated called the Veillées du bon vieux temps, often and typically included a combination of performers. This article examines Barbeau’s “performers,” including classically educated musicians and some of his most prolific, talented informants.